The mystery of Local Cosmic Void - Franco, C.; Avila, F.; Bernui, A. (Cadernos de Astronomia, 2024)
The flat-ΛCDM Model (Λ is the cosmological constant and CDM, cold dark matter) is the model that best fits currentobservational data. It is based on the Cosmological Principle, which assumes statistical homogeneity and isotropy ofthe universe on a large scale. Studying the properties of the latter in the Local Universe (LU) through the ALFALFAcatalog (Arecibo Legacy Fast ALFA Survey) – a survey that covers ∼ 7000 deg2 of the sky and has 31502 extragalacticsources of HI, distributed in the interval 0 < z < 0.06 and divided between the North and South Galactic hemispheres –we found results that indicate the existence of a region containing few galaxies, and which was first described by Tully& Fischer (1987), becoming known as the Local Cosmic Void. Our analyzes are model-independent and use the two-point angular correlation function (2PACF) as a statistical gauge, in addition to lognormal simulations (which considercosmological parameters) to estimate the uncertainties of the results. To understand the properties and morphology of thestructure found, we carried out tests with simulated voids, in addition to comparative investigations with the descriptionsof LU voids available in the literature. Our results indicate that the LCV has a numerical density contrast of δ ≃ −0.3,corresponding to a subdensity of ∼ 150 Mpc in length and width of ∼ 60 Mpc , characteristics that agree with the literature.
Keywords: cosmology; standard model; local void